Non‐Metabolic Uptake of Al3+ by Dead Leaves of Rubus ulmifolius: Comparison With Metabolic Bioaccumulation Data. Issue 2 (12th December 2015) - Lodeiro, Pablo; López‐García, Marta; Herrero, Luz; Barriada, José L.; Herrero, Roberto; Carro, Leticia; Vilariño, Teresa; Rodríguez, Pilar; Sastre de Vicente, Manuel E.
Abstract : This paper reports a physicochemical study (thermodynamic and kinetic data) describing the ability of Rubus ulmifolius biomass (dead leaves) for metal uptake. The toxicity of aluminum is a major problem for crops in acidic soils and therefore, aluminum has been selected. The results obtained indicate that dead R. ulmifolius leaves uptake up to 10 000 mg/kg on its surface in less than 60 min. This suggests that R. ulmifolius can be an excellent component with adsorbent properties for aquatic environments and in particular for amendments to be used in acidic soils in order to control aluminum levels, thus its toxicity. The results obtained have been critically analyzed and compared with literature on aluminum bioaccumulation. The application of a pseudo‐second order kinetic equation, not previously used in toxicity studies, is discussed. Moreover, a good linear correlation between stability constants for Al 3+ complexes with several defined ligands and the Langmuir affinity constants obtained from the corresponding adsorption isotherm has been found. Therefore, in addition to its ethno‐botanical relevance, applications of R. ulmifolius as a detoxifier for aluminum in a simulated acidic gastrointestinal fluid, as phytostabilization agent in amendments or in natural attenuation cycles or as biomass for wastewater treatment containing aluminum, are suggested. Abstract : Rubus ulmifolius leaves can act as a potential adsorbent for aluminum removal in relatively acidic environments (pH 2.5–4). A comparative analysis with aluminum bioaccumulation published data allows concluding the utility of the pseudo‐second order equation in the interpretation of metabolic uptake of this metal, not previously suggested and with some interest in the interpretation of Al 3+ tolerance by plants.